The Role of Mindfulness in Student Emotional Regulation and Academic Achievement: A Review of the Literature - Aluintany, Vitasha Geushiria; Wijayati, Nanik; Sumartiningsih, Sri; Yuwono, Agus (Universitas Pahlawan Tuanku Tambusai, 2025)
This study is a literature review that aims to examine the role of mindfulness in the regulation of emotions and its relation to students' academic achievement. Studies have shown that mindfulness can improve self-awareness, acceptance without judgment, as well as the ability to be present in the present moment. These abilities contribute significantly to healthier and adaptive emotional management. This study uses a literature review approach with a systematic review type to understand the relationship between mindfulness, emotion regulation, and student academic achievement. The study relies on scientific articles published between 2020 and 2025 and obtained from trusted sources such as PubMed, ScienceDirect, SpringerLink, Google Scholar, and DOAJ with relevant keywords. Good emotional regulation allows students to be more focused, calm, and resilient in the face of learning pressure, which ultimately has a positive impact on academic achievement. The review also highlights the importance of implementing mindfulness programs in elementary school settings as part of efforts to improve psychological well-being and learning quality. Based on the results of the study, it is recommended that mindfulness be one of the approaches that can be integrated into learning strategies to support students' emotional and academic development in a balanced manner.